Correlation of Patient Visits with Diabetes Mellitus and Hypertension and Patient Anxiety During Covid-19 - Panca Radono; Yatimah Yatimah (Sean Institute, 2026)
The COVID-19 pandemic has had a big effect on the use of primary healthcare services. For example, fewer people with degenerative diseases like diabetes mellitus and hypertension are going to see their doctors. People may be worried about getting COVID-19, which could make them less likely to go to their regular check-up appointments, especially at the Community Health Center (Puskesmas) level. This study seeks to examine the correlation between the frequency of visits by patients with hypertension and diabetes mellitus and their anxiety levels during the COVID-19 pandemic in the Sukorejo Community Health Center (Puskesmas) area of Blitar City. This research employed a quantitative correlational design utilizing a cross-sectional methodology. The study sample comprised 60 respondents, chosen via simple random sampling from the population of patients diagnosed with hypertension and diabetes mellitus. The Hamilton Rating Scale for Anxiety (HARS) questionnaire was utilized to assess anxiety levels, and a structured questionnaire was employed to gather information regarding patient visits. We used the Chi-Square test with a significance level of 0.05 to analyze the data. The findings indicated that a significant proportion of respondents (68.3%) did not frequently visit the Puskesmas during the COVID-19 pandemic. Most of the people who answered the question said they were not anxious (48.3%) or slightly anxious (28.3%). The chi-square test yielded a p-value of 0.364 (p > 0.05), signifying no significant correlation between patient visits and anxiety levels during the COVID-19 pandemic. It can be determined that anxiety levels were not a significant factor affecting the visits of patients with hypertension and diabetes mellitus during the COVID-19 pandemic. The results indicate the necessity for enhanced health education, familial support, and better accessibility and quality of healthcare services to promote compliance with regular visits by patients with degenerative diseases.